Autonomy in teaching and learning English at the advanced level – between theory and practice - Aleksandrzak, Magdalena (Wydawnictwo Naukowe UAM, 2010)
The present article concentrates on the concept of learner autonomy as an increasingly popular trend in language learning and teaching. The paper discusses the importance of language awareness training, the new roles of the teacher and presents the forms of evaluation typical of autonomous learning environments. It also suggests some solutions for the classroom practice which seem most effective in promoting learner autonomy at the advanced level of language proficiency and briefly examines the research findings in the field.
Keywords: Learner autonomy; Language awareness; Self-assessment